Broadband High Frequency Power Conversion With Frequency-Tuning Matching Network - ZHECHI YE; Juan Rivas (IEEE Open Journal of Power Electronics)
Varying load impedances challenge high-frequency resonant converter operation, but existing matching network solutions are typically slow, lossy, or complex in design. We propose a novel general method to design matching networks that can match a varying impedance to a near-constant value by adjusting only the frequency. To drive the proposed frequency-tuning matching network (FTMN), we present a systematic approach to designing broadband power inverters that can be applied to various topologies. We demonstrate two broadband power converters with a class-E and a class- $Φ _{2}$ topology, respectively. With the FTMN, both converters can achieve around 90% efficiency when driving a varying plasma load impedance with a tuning frequency of around 13.56 MHz.